The Relationship Between On The Job Training And Employee Competency Test Results At Pt Elnusa Petrofin Bungus Teluk Kabung Padang - Pramutia, Intan; 'Aini, Wirdatul (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
The background of this research is competency test results employee at PT Elnusa Petrofin Bungus Teluk Kabung Padang, this is suspected because of on-the-job training. This research aims to reveal the description of on-the-job training, employee competency test results, and see the relationship between on-the-job training and competency test results employee at PT Elnusa Petrofin Bungus Teluk Kabung Padang. This research uses a quantitative approach with types correlational research. The population in this study was 608 employees (tank car crew). A sampling technique uses random sampling. A sample was drawn from a population of 85 using the Slovin method. The data collection process uses questionnaires. Data analysis techniques use percentage formulas and product correlation formulas moments. The results of this research show that: (1) on-the-job training those carried out by employees ; (2) competency test results employees at PT Elnusa Petrofin Bungus Teluk Kabung Padang ; (3) there is a significant relationship between on-the-job training with the results of employee competency tests at PT Elnusa Petrofin Bungus Teluk Kabung Padang.